Blockholder Ownership, Independent Commissioner Experience, and Director Experience In Improving Company Performance: A Corporate Governance Perspective - Alriansyah Manurung, Muhammad Rizqi (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
Detailed instructions for preparing your paper for submission to This study examines the impact of corporate governance mechanisms specifically blockholder ownership, independent commissioner experience, and director experience—on company performance in Indonesian manufacturing firms listed on the Indonesia Stock Exchange between 2020 and 2023. The objective is to understand how these governance variables contribute to improving company outcomes, particularly in emerging markets with unique governance challenges. Using secondary data from financial reports and corporate filings, the study employs regression analysis to assess the relationships between these variables and company performance. The results show that blockholder ownership has a limited effect on company performance, likely due to governance challenges such as weak regulatory frameworks and conflicting interests among blockholders. Conversely, independent commissioner experience significantly enhances company performance by improving strategic decision-making and reducing agency costs. Similarly, the collective experience of the board positively influences performance, with experienced directors better equipped to navigate business challenges and make informed decisions. In conclusion, the study highlights the critical role of strong corporate governance in shaping firm performance. It recommends that firms in emerging markets optimize governance structures by ensuring alignment between blockholders and management, prioritizing the recruitment of experienced independent directors, and fostering a diverse and experienced board to drive long-term success. These findings have practical implications for policymakers, regulators, and corporate boards aiming to enhance organizational outcomes in emerging markets.